Cyber privacy : who has your data and why you should care - Doss, April Falcon, 1967- (Dallas, TX : BenBella Books, Inc., 2020)
"April Falcon Doss, a cybersecurity and privacy expert with experience working for the NSA and the US government, explores the most common types of data being collected about individuals today and delve into how it is being used-sometimes against us-by the private sector, the government, and even our employers and schools".
Includes bibliographical references (p. 307-340) and index.
Keywords: Privacy, Right of -- United States; Data protection -- United States; Computer security -- United States